Development of emotional intelligence in pre-service teachers’ to increase professional well-being - Valente, Sabina (2022)
Teaching is a demanding profession, thus is a need to acknowledge the complexities of this job and care for teachers’ well-being. Well-being is fundamental to their professional success and also to the development of their students. Teachers increasingly respond to demanding classroom situations and many of these lead to emotional distress and have serious consequences for their health. In this sense, it is increasingly necessary to have tools to respond to emotional situations in the classroom and to know how to better manage emotions. So, the way teachers handle their emotions and those of their learners is central to the success of their well-being. Studies show that emotionally intelligent teachers stay emotionally healthy since emotional abilities protect the teachers’ well-being. Focused on the emotional intelligence role in teachers’ well-being, this opinion paper presents the importance of developing emotional skills in pre-service teachers’ to increase professional well-being. Thus, new model of training for pre-service teachers’ is needed that includes the promotion of emotional skills through the benefits they present to their professional well-being.